The Effect of Hybrid Instruction on Students’ Reading Comprehension in SMA 4 Kendari - Salim, Fadlan; Tambunan, Tambunan; Badara, Aris (Halu Oleo University, 2019)
Hybrid instruction is a learning model which combines face-to-face mode and online learning. The use of this method is highly compatible with the teaching of English in Indonesia. This study was set out to investigate the impact of hybrid instruction on students’ reading ability. Results of data analysis showed that there was a significant difference between the gain score of students in the experimental class and that of their cohort in the control class. In addition, in regard to the students’ motivation to learn using the hybrid instruction, it appeared that the students were highly motivated not only extrinsically but also intrinsically, which meant that both main elements of motivational types according to Self-determination Theory had been addressed